2008
DOI: 10.1111/j.1440-1843.2008.01355.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between field walking tests and incremental cycle ergometry in COPD

Abstract: The significant relationships found between the three exercise tests, and the regression equations predicting peak work rate on the CET from the 6MWT or the ISWT, may allow for the estimation of intensity of cycle exercise training from walk tests in COPD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
122
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(136 citation statements)
references
References 31 publications
(47 reference statements)
9
122
1
4
Order By: Relevance
“…In a study by POULAIN et al [16], 28% of patients with COPD exhibited desaturation on 6MWT that was not observed on CPET. Other authors have reported similar findings [35,37,38]. The phenomenon was reproducible and not protocol dependent, emphasising the clinical interest of the 6MWT [16].…”
Section: Oxyhaemoglobin Saturationsupporting
confidence: 69%
“…In a study by POULAIN et al [16], 28% of patients with COPD exhibited desaturation on 6MWT that was not observed on CPET. Other authors have reported similar findings [35,37,38]. The phenomenon was reproducible and not protocol dependent, emphasising the clinical interest of the 6MWT [16].…”
Section: Oxyhaemoglobin Saturationsupporting
confidence: 69%
“…The 6MWD may reflect the maximum exercise capacity, as do peak work rate and ISWT. 26,27 On the other hand, ET measures the ability to sustain submaximal exercise capacity. 10 ET can improve even if there is no significant increase in maximum exercise capacity.…”
Section: Discussionmentioning
confidence: 99%
“…31 In addition, the correlation we observed between number of steps and peak work load in the cycling test (r ϭ 0.69) was similar to that reported in studies of peak work load in the 6-min walk test versus the shuttle test. 32,33 Therefore the number of steps climbed in the Chester step test can be representative of functional performance, and, when tests that require long corridors are unfeasible, step tests may be an alternative. However, further studies are needed to establish a better incremental pattern for patients with chronic respiratory diseases, once it has been demonstrated that variations of incremental size affect exercise time in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%